2007
DOI: 10.1182/blood-2007-04-084434
|View full text |Cite
|
Sign up to set email alerts
|

A novel erythrocytosis-associated PHD2 mutation suggests the location of a HIF binding groove

Abstract: The molecular basis of the erythrocytosis group of red cell disorders is incompletely defined. Some cases are due to dysregulation of erythropoietin (Epo) synthesis. The hypoxia inducible transcription factor (HIF) tightly regulates Epo synthesis. HIF in turn is regulated through its ␣ subunit, which under normoxic conditions is hydroxylated on specific prolines and targeted for degradation by the von Hippel Lindau (VHL) protein. Several mutations in VHL have been reported in erythrocytosis, but only 1 mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 19 publications
4
103
3
Order By: Relevance
“…All the three new erythrocytosis-associated PHD2 mutations here reported involve the catalytic domain of the protein and add to those already known (Figure 2A-B). [16][17][18][19] We previously described as mutation a germ-line missense substitution, 20 Q157H, found in association with JAK2 V617F in a propositus with polycythemia vera and found in an isolated form also in his son, presenting only with mild erythrocytosis. Q157H has been reported also as SNP (NCBI entry, rs61750991) with a frequency of around 2% in normal subjects but with a much higher frequency in cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…All the three new erythrocytosis-associated PHD2 mutations here reported involve the catalytic domain of the protein and add to those already known (Figure 2A-B). [16][17][18][19] We previously described as mutation a germ-line missense substitution, 20 Q157H, found in association with JAK2 V617F in a propositus with polycythemia vera and found in an isolated form also in his son, presenting only with mild erythrocytosis. Q157H has been reported also as SNP (NCBI entry, rs61750991) with a frequency of around 2% in normal subjects but with a much higher frequency in cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…17,22 EpoR mutations are also rare and account for the erythrocytosis in only a minority of cases. Studies that have included cases of familial erythrocytosis have suggested a prevalence of 12-15%, [23][24][25] whereas another study found only one EpoR mutation in 100 IE cases.…”
Section: Discussionmentioning
confidence: 99%
“…pFastBac-HT-HA-p23 was constructed by subcloning the 0.5-kb BamHI/XhoI fragment of pcDNA5/ FRT/TO-3ϫFlag-p23 into the BamHI/XhoI site of pFastBac-HT-HA-VHL. The sources of pGEX-HIF-1␣ (531-575), pGEX-HIF-2␣ (516 -549), and all other plasmids have been described (19,26).…”
Section: Methodsmentioning
confidence: 99%